PREDICTORS AND CORRELATES OF SELF-ESTEEM IN DEAF ATHLETES - Uchida, Wakaki; Marsh, Herbert; Hashimoto, Kimio (European Journal of Adapted Physical Activity, 2015)
The aims of this study were to examine the association between different aspects of self-esteem and level of sport competition and to assess the associations between self-esteem and age, length of participation in sport, and number of dramatic sport experiences in deaf athletes. One hundred and twelve congenitally deaf Japanese athletes completed the Self-Positiveness Scale (SPS) and the Inventory of Dramatic Experience for Sport (IDES). A correlational analysis demonstrated moderate to weak relationships between all of the SPS subscales except self-acceptance and public self-consciousness. One-way ANOVAs revealed that international athletes had fewer negative relationships with others and more dramatic sport experiences. Multiple regression analysis indicated that dramatic sport experiences significantly predicted self-acceptance, self-achievement, life satisfaction, negative relationships with others, and self-disclosure. Thus, dramatic sport experiences can enhance some aspects of self-esteem.
Keywords: dramatic sport experiences; level of competition; duration of sport participation